Cucurbitacin B induces inhibitory effects via the CIP2A/PP2A/C-KIT signaling axis in t(8;21) acute myeloid leukemia - Wenjing Ma; Yuchen Xiang; Rui Yang; Te Zhang; Jiaxin Xu; Yezi Wu; Xuewen Liu; Ke Xiang; Huzi Zhao; Ying Liu; Yuan Si (Elsevier, 2019)
Acute myeloid leukemia (AML) is the most common subtype of hematological malignancy in humans, and its incidence increases with age. The treatment of AML still faces challenges. Therefore, there is an urgent need to develop more effective targeted therapies. The receptor tyrosine kinase C-KIT confers critical proliferative signals to AML. Cancerous inhibitor of protein phosphatase 2A (CIP2A) is an endogenous inhibitor of protein phosphatase 2A (PP2A), which promotes the growth and transformation of various solid tumors. These actions make CIP2A a promising target for tumor treatment. Here, we reported the effects and underlying mechanisms of a natural compound, cucurbitacin B (CuB), on AML. We reported that CuB suppressed growth and induced apoptosis in AML cells. The inhibition of growth and activation of apoptosis were mediated through CuB-induced downregulation of the CIP2A/PP2A/C-KIT signal pathway. Furthermore, CuB inactivated the JAK2 and STAT3 molecules downstream of C-KIT via the downregulation of CIP2A. These results advance our understanding of CuB-induced growth inhibition and apoptosis and support further investigation of CuB as a CIP2A inhibitor for AML therapies. Keywords: Cucurbitacin B, Acute myeloid leukemia, CIP2A, C-KIT, PP2A